Investigating of climate factors associated with the number of COVID-19 incidences in Saudi Arabia. (13th April 2022) - Alkabaa, Abdulaziz S.
This study investigates the possible association between the climate variables of daily average temperature (°C), relative humidity (%), wind speed (mph), air pressure (mmHg), and the number of COVID-19 incidents in five main cities in Saudi Arabia. Furthermore, other non-climate factors that might influence the number of COVID-19 incidents, such as region, day type, and conducted number of COVID-19 tests (massive testing levels), are included in the model. A negative binomial regression model is applied to study the association between the climate and non-climate factors affecting COVID-19 cases for 75 days with an average temperature range of (18-36)°C. Results show significant findings that the only climate factor affecting the COVID-19 numbers is the average daily temperature. The regression model shows a significant positive association between average daily temperature and the COVID-19 incidents by increasing 6.1% in the number of COVID-19 cases for each extra 1°C average temperature increase.